Strategy for the development of the food industry in Ukraine - Yeremenko, O.; Kunytsia, Lyudmila (My University, 2019)
The solution of the topical problems of the strategy of development of the food industry in Ukraine may be the establishment of export of products with a decrease in its cost.
Keywords: food industry; development; strategy; харчова промисловість; розвиток; стратегія; кафедра ділової іноземної мови та міжнародної комунікації